Students’ Satisfaction of Online Learning During COVID-19 Pandemic - Silvani Safitri; Sriati Usman; Abdul Kamaruddin; Anshari Syafar; Aminah (Universitas Tadulako, 2021)
This research aims to find out the students' satisfaction of online learning and the factors that affect the students’ satisfaction of online learning during the COVID-19 Pandemic at Tadulako University in the academic year 2020/2021. This research used qualitative approach. This research collected the data through survey method using a questionnaire and interview. The research subject was the third year students of the English Language Education program at Tadulako University in the academic year 2020/2021. The samples were selected using purposive sampling to choose the students as the respondents. The result indicated that the students' satisfaction of online learning during the COVID-19 Pandemic is 62.13%, which wasconsidered satisfied. Percentages for each factor were described as follow; 66.37% or equivalent as satisfied for Student-Lecturer Interaction, 67.64%or equivalent as satisfied for Instructional Materials, 61.95% for Online Learning Platformor equivalent as satisfied, and 51,54% for Functionality or equivalent as dissatisfied. So, three factors are satisfied, and one factor is dissatisfied. The result stated as 'satisfied' dominates the result of the students' responses; it can simply conclude that those factors affect the students' satisfaction of online learning during the COVID-19 Pandemic.